Someone to Look Up To: Executive–Follower Ethical Reasoning and Perceptions of Ethical Leadership. (March 2013) - Jordan, Jennifer; Brown, Michael E.; Treviño, Linda K.; Finkelstein, Sydney
Despite a business environment that highlights the importance of executives' ethical leadership, the individual antecedents of ethical leadership remain largely unknown. In this study, the authors propose that follower perceptions of ethical leadership depend on the executive leader's cognitive moral development (CMD) and, more importantly, on the relationship between executive leader and follower CMD. In a sample of 143 leader–follower dyads, the authors find a direct positive relationship between leader CMD and perceptions of ethical leadership. Using polynomial regression, they find that ethical leadership is maximized when the leader's CMD diverges from and is greater than the follower's CMD. The authors explain these findings using a social learning theory framework. Leaders who are more advanced ethical reasoners relative to their followers are likely to stand out as salient ethical role models whose ethics-related communication and behavior attract followers' attention. The authors discuss the research and practical implications of these findings.